A case of delayed distal coil migration after coil embolization of an unruptured distal azygos anterior cerebral artery aneurysm: A case report and literature review. Issue 6 (December 2018) - Maeda, Kazushi; Motoie, Ryota; Karashima, Satoshi; Otsuji, Ryosuke; Ren, Nice; Nagaoka, Shintaro; Ikai, Yoshiaki; Uno, Junji; Gi, Hidefuku
Intraprocedural coil migration during endovascular treatment for an aneurysm that might carry serious ischemic complications is well known. On the other hand, delayed coil migration after endovascular treatment for an aneurysm is very rare. A 77-year-old woman was incidentally diagnosed with unruptured aneurysm associated with distal azygos anterior cerebral artery (ACA). The aneurysm was located at the distal bifurcation of the azygos ACA and was wide necked (approximately 7 mm in diameter). Endovascular coil embolization was selected and the aneurysm was occluded successfully, but 29 days after endovascular therapy, follow-up computed tomography (CT) and magnetic resonance (MR) angiography revealed distal coil migration in the peripheral portion of the ACA. In addition, CT on day 57 after therapy revealed the migrated coil had moved more distally. Fortunately, in the course of these events, the patient remained asymptomatic. To the best of our knowledge, this represents the first case of delayed distal coil migration associated with relatively rare azygos ACA aneurysm, and also the first report confirming more distal coil movement over time. In the future, a large number of patients could develop this complication as more aneurysms are aggressively treated with endovascular treatment. Knowledge regarding the possibility of delayed coil migration is thus important.